The media image of Ukraine: An European view - Tkachenko, Olena H.; Sydorenko, Olha P.; Melnikova, Iuliia O.; Myronets, Nina R.; Smus, Andrii H. (Linguistics and Culture Review, 2021)
A positive image of the country on the international arena enables the state to pursue an active foreign policy, attract investment and tourist flows, and increase its prestige in the world. A positive political, economic, social, and cultural reputation in the world is very important for Ukraine, which is in a state of political crisis, military conflict in the East of the country, and at the same time has declared to uphold the European values and is aimed at joining the EU and the NATO. Ukraine is an attractive source of news in shaping the agenda of influential European media. In 2019, the catalyst of interest was the events of the presidential election campaign. This is one of the fateful periods of the country’s struggle for independence and democracy. The political course of the country in the international arena depends on the results of the will expression, which may indirectly affect the geopolitical landscape of Europe. Based on the content analysis of The Telegraph, The Guardian (UK); Die Zeit, Die Tageszeitung (Germany); Le Figaro, Le Monde (France) defined the semantic structure and emotional and evaluative tone of the media image of Ukraine.